Sisu : road to revenge [videorecording (DVD)] - Tommila, Jorma, 1959-; Brake, Richard, 1964-; Lang, Stephen, 1952-; Orasmaa, Mika; Küngas, Pille; Seppä, Juri; Wäinölä, Tuomas, 1976- (Sony Pictures Home Entertainment, 2026)
"Returning to the house where his family was brutally murdered during the war, 'the man who refuses to die' dismantles it, loads it on a truck, and is determined to rebuild it somewhere safe in their honor. When the Red Army commander who killed his family comes back hellbent on finishing the job, a relentless, cross-country chase ensues."--